Boundedness of Marcinkiewicz Integrals and Their Commutators on Generalized Weighted Morrey Spaces - Runqing Cui; Zhang Li (Journal of Function Spaces)
We will study the boundedness of Marcinkiewicz integrals with rough kernel on the generalized weighted Morrey spaces. We will also prove that the commutator operators formed by a BMORn function and Marcinkiewicz integrals are also bounded on the generalized weighted Morrey spaces.